The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4103/ijo.ijo_368_21
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the postoperative effect of corneal cross-linking on keratoconus using the ABCD grading system

Abstract: Purpose: To monitor the changes in the ABCD grading system during a one-year follow-up after a corneal cross-linking (CXL) procedure. Methods: This prospective study included 30 eyes of 25 patients with keratoconus, who received the CXL treatment. The patients with a history of ocular trauma or surgery and other corneal pathology were excluded from the study. The patients were examined at the baseline visit and followed up at 3, 6, and 12 months after the CXL. All the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the literature, only a few studies evaluated the applicability of the ABCD staging system in monitoring the efficacy of the standard procedure. In contrast, only one recently published retrospective study investigated its utility in evaluating accelerated protocols and compared the effectiveness of different protocols regarding the ABCD grading system [ 8 , 39 , 40 , 41 , 42 , 43 ]. Danesh and coauthors showed no significant changes in parameters A and D, while parameters B and C significantly increased one year after conventional CXL [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, only a few studies evaluated the applicability of the ABCD staging system in monitoring the efficacy of the standard procedure. In contrast, only one recently published retrospective study investigated its utility in evaluating accelerated protocols and compared the effectiveness of different protocols regarding the ABCD grading system [ 8 , 39 , 40 , 41 , 42 , 43 ]. Danesh and coauthors showed no significant changes in parameters A and D, while parameters B and C significantly increased one year after conventional CXL [ 8 ].…”
Section: Discussionmentioning
confidence: 99%